2009
DOI: 10.1167/iovs.08-2521
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Retinal Neovascularization by Erythropoietin siRNA in a Mouse Model of Proliferative Retinopathy

Abstract: Purpose Erythropoietin (EPO), an oxygen-regulated hormone stimulating erythrocyte production, was recently found to be critical for retinal angiogenesis. EPO mRNA expression levels in retina are highly elevated during the hypoxia-induced proliferation phase of retinopathy. The authors investigated the inhibition of retinal EPO mRNA expression with RNA interference as a potential strategy to suppress retinal neovascularization and to prevent proliferative retinopathy. Methods The authors used a mouse model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 26 publications
8
131
0
2
Order By: Relevance
“…This study provided the first evidence that EPO acts on the angiogenic pathway independently from VEGF and is more strongly correlated with the presence of PDR than VEGF (Watanabe et al 2005). Subsequent studies have shown genetic mutations can increase EPO expression and this is associated with increased risk of PDR and related condition in patients and in animals (Tong et al 2008;Chen et al 2009;Xiong et al 2009;Abhary et al 2010).…”
Section: Angiogenic Mechanisms In Proliferative Diabetic Retinopathymentioning
confidence: 74%
“…This study provided the first evidence that EPO acts on the angiogenic pathway independently from VEGF and is more strongly correlated with the presence of PDR than VEGF (Watanabe et al 2005). Subsequent studies have shown genetic mutations can increase EPO expression and this is associated with increased risk of PDR and related condition in patients and in animals (Tong et al 2008;Chen et al 2009;Xiong et al 2009;Abhary et al 2010).…”
Section: Angiogenic Mechanisms In Proliferative Diabetic Retinopathymentioning
confidence: 74%
“…Intravitreal injections were performed following established protocols (49,50). We injected 1 μg of miR-150 mimics (Ambion) using a 33-gauge needle behind the limbus of the eye, and the contralateral eye of the same animal was injected with an equal amount of negative control mimics.…”
Section: Methodsmentioning
confidence: 99%
“…Endogenous EPO in the retina is crucial for retinal angiogenesis (10,20). A previous study showed that mRNA expression of EPO is increased greatly in the second phase of retinopathy (12). After intravitreal injection of small interference RNA (siRNA), expressions of EPO as well as RNV are significantly suppressed through RNA interference.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, suppression of EPO would be beneficial for the inhibition of retinal pathological vessels in the second phase (12). Intravitreal injection of small interference RNA is effective in hindering the development of RNV (12). Moreover, a recent study indicated that early EPO administration did not raise the risk of ROP (13).…”
Section: Introductionmentioning
confidence: 99%